2021
DOI: 10.1021/acs.jpcc.1c03623
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Pristine and Carboxylate-Covered Anatase TiO2(001) in Aqueous Environment

Abstract: The interactions of carboxylic acids and water with TiO 2 surfaces are important in applications ranging from solar cells to biomedical devices. Here we focus on the aqueous interface with the minority (001) surface of anatase TiO 2 (A-001) and the behavior of adsorbed formic and acetic acid monolayers at this interface. We investigated the structure and stability of the pristine reconstructed and formic/acetic acid covered A-001 surfaces in contact with water using density functional theory (DFT) calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…This is because the reconstruction typically happens under vacuum condition at high temperatures, which does not agree with the current preparation condition. In addition, previous STM work and DFT calculation work indicated that carboxylic acid only dissociatively adsorbs on the ridge sites, while it molecularly adsorbs on the terrace sites, 80,81 which would result in molecularly adsorbed propionic acid as the dominant surface species. This expectation is in contrast with the FTIR results which showed that molecularly adsorbed propionic acid is only a minor species (Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 98%
See 1 more Smart Citation
“…This is because the reconstruction typically happens under vacuum condition at high temperatures, which does not agree with the current preparation condition. In addition, previous STM work and DFT calculation work indicated that carboxylic acid only dissociatively adsorbs on the ridge sites, while it molecularly adsorbs on the terrace sites, 80,81 which would result in molecularly adsorbed propionic acid as the dominant surface species. This expectation is in contrast with the FTIR results which showed that molecularly adsorbed propionic acid is only a minor species (Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 98%
“…This result is in good agreement with a previous work of formic and acetic acids adsorption on (001) surface as a function of coverage. 80 To determine the extent of surface stabilization upon adsorption of propionic acid, the surface energy was calculated. As reported in Table S2, † the surface energy of (001) decreases with increasing propionate coverage, which is consistent with previous work.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Simulations of these adsorbed monolayers in water demonstrate that some protons are released into the water, creating a negatively charged surface with solvated H 3 O + ions. HCOOH also adsorbs in BD form on anatase (001) surface adsorbed with H 2 O 258 . Using DFT and AIMD methods, Zeng et al 258 found two types of BD adsorptions featured by BD bridging and BD straddling.…”
Section: The Adsorption Activation and Reaction Of Organic Moleculesmentioning
confidence: 99%
“…HCOOH also adsorbs in BD form on anatase (001) surface adsorbed with H 2 O 258 . Using DFT and AIMD methods, Zeng et al 258 found two types of BD adsorptions featured by BD bridging and BD straddling. The latter is found to rapidly transform into a monodentate structure during the simulations in an aqueous environment.…”
Section: The Adsorption Activation and Reaction Of Organic Moleculesmentioning
confidence: 99%
“…All publication charges for this article have been paid for by the Royal Society of Chemistry performed at each timestep of the MD simulations, making this method applicable to complex systems that involve chemical bond breaking/formation with a high degree of accuracy. DFT-MD simulations have been successfully applied to various liquid/metal oxide interfaces, and in particular, for water interfaces, simulations for TiO 2 , [7][8][9][10][11] CeO 2 , [12][13][14][15] Al 2 O 3 , [16][17][18][19][20] ZnO, 21,22 ZrO 2 , 23 etc. have been reported, and the interface structures and hydrogen bond networks, including the proton hopping mechanism, have been scrutinized in these studies.…”
Section: Introductionmentioning
confidence: 99%